Current Problems in Teaching Physical Education - Bakhromovich, Rakhmankulov Zamir (Researchparks Publishing, 2023)
In the article, the fundamental reforms carried out in the field of physical education, the goals and objectives of public events in the fields of culture, medicine, education and sports, their content is the comprehensive maturity of young people studying for a profession, and their full response to the students of the time. such issues are covered.